Deciphering synergetic core-shell transformation from [Mo6O22@Ag44] to [Mo8O28@Ag50] - Zhi Wang (Nature Portfolio, 2018)
Understanding how one metal nanocluster transforms into another is of synthetic and fundamental importance. Here, the authors use mass spectrometry to reveal an acid-induced structural transformation between two Ag clusters that proceeds via a breakage-growth-reassembly mechanism.